О новой находке куторы малой на Украине - Абеленцев, В.И. (Вестник зоологии, 1967)
For a long time the scientists consider that Neomys anomalus Cabrera inhabits Europe only up to the Dnieper (Abelentsev, Pidoplichko, 1956). Some single finds are known eastwards in Borispol (Korneyev, 1965), Brovary and Yagotin district of Kiev region, near Poltava, in the South of Kherson and the Crimean region. Neomys anomalus Cabrera was found by the authors in the flood-lands of Seversky Donets river (Chernikovo lake) on the territory of Srebryanskoe forestry (Lugansk region), where from the 30th of August to the 4th of September, 1961 three fe-males and a male were catched. The article contains some data of the other insectivorous and Muridae animals (number, inhabition). On the basis of measuring and craniometric indeces the author attributes the Neomys anomalus Cabrera from the Seversky Donets to the smallest subspecies —Neomys anomalus milleri Mattaz. whereas the animals from the south regions of the Ukrainian SSR are presented by a big form of Neomys anomalus mokrzeckii Martin o. The finds of Neomys anomalus Cabrera in the east of the Ukraine and in Usmansky forest of Voronezh region of the RSFSR (the Lavrov's, 1938) move far to the east the lines of an areal, and so, change the existing ideas about the spreading and inhabition of this rarest for East Europe species.